FUNGSI TIROID PADA ANAK OBESITAS - Sitompul, Dame Lamtiur; dr, Hakimi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Levels of Thyroid Stimulating Hormone (TSH) can have a positive correlation with Body Mass Index(BMI), which is found TSH levels increased slightly with increased leptin in obese children. Increasing ofTSH, Free Triiodotironine (FT3) and leptin levels in obese children and their weight loss causes adecrease in serum TSH, FT3, and leptin levels, supporting the hypothesis that alterations in thyroidfunction in obesity are reversible with weight loss.Keywords: thyroid function, obesity, children